Політична міфологія: проблема визначення - Ситник, О. В.; Sytnyk, O. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті висвітлено проблеми дослідження політичної міфології в сучасній філософській і політичній думці. Проаналізовано поняття, структуру й функцію політичного міфу. Ihe article analyzes to a problem of research of political mythology in modern philosophical and politological thought. Тhe concept, structure and functions of a political myth a re considered. Political myth is defined as a myth used to implement the objectives of the struggle for political power, legitimizing power of the political domination. Justified reasons for the revival of myth , mythological component of the mass consciousness. Empathy political myth - the first prerequisite of legitimizing the mass consciousness of government institutions and individuals who as characters of this power. In the myth, to communicate directly with the personal experience of collective experience. Myth is valid for the person only to the extent that a person feels in her presence of at least one answer to the vital question for yourself . Myth – a form of practical spiritual understanding of reality, the specificity of which is revealed in the transcoding consciousness facts of reality, that the events and phenomena of reality modeled and represented in a different plane of reality .Political myth as a way of sacralization of power is the basis sakralizatsionnyh processes in modern society. He «sprayed» in a culture that is its bearer . Political myth has its own structure and functions, the most important of which is the legitimization of government institutions and the supreme ruler .
Political Mythology: the Problem of Definition
Keywords: політична міфологія; political mythology; влада; power; суспільна свідомість; public consciousness